To Assess the Impact of the Nurse-Patient Relationship on Health Care Outcomes at Tertiary Care Hospital - Sanaullah; Faique Ali Kalhoro; Aisha Sahoowal; Abu Baker; Mehwish Mumtaz; Habib Ahmed (Indus Journal of Bioscience Research, 2025)
Introduction: Nursing is based on care, trust, and empathy. Patient-centered care involves the integration of patients into their care. Empathy in nursing practice establishes rapport and relates to the patient’s needs. Increased empathy results in increased patient relationships and experiences with the illness. Methodology: A descriptive cross-sectional study was conducted from September 2023 to December 2023 at Liaquat University Hospital. The study utilized an adapted questionnaire with Likert scale responses, encompassing fifteen items across five dimensions related to nurse-patient interactions. Nurses willing to participate, both male and female, with at least two years of working experience, aged between 25 to 55 years were included. On the other hand, nurses under the age of 25, with less than two years of experience, and unwilling to participate were excluded. Results: A total of 104 nurses participated in the study conducted at Liaquat University Hospital, Hyderabad. The mean age of respondents was 36.6±9.83 years, among the participants, 59.1% were female and 40.9% were male. The majority of participants were staff nurses (90.9%), with a small percentage being head nurses (9.1%).In terms of educational background, 65.90% of participants held diplomas, 22.7% held Bachelor of Science in Nursing (BScN) degrees, 6.8% held Master of Science in Nursing (MScN) degrees, and 4.6% had other educational qualifications. Conclusion: This study underscores the importance of strong connections between nurses and patients, touching on aspects such as patient-centered care and satisfaction.